The Implementation of “Guru Penggerak” (Organizer Teachers) Concept to Innovation of The Discussion Methods in Thermodynamics Course - Ahmad Farhan; Fitria Herliana; Evendi Evendi; Nia Kurnia Devy; Fida Mauliza (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
The thermodynamics lecture process in odd semester 2019/2020 at the Physics Education Department of FKIP Unsyiah is divided into three stages based on the lecture method used, namely; (1) lecture method, virtual experiments, and discussions, (2) assignments and group presentations, and (3) innovative discussions inspired by the idea of ​​a “Guru Penggerak.” Modification from the innovation of the discussion method is carried out by the strategy of (a) not limiting the topic of discussion, (b) online discussion using WhatsApp (WA) group lectures. The study was conducted to determine the response of students to the innovations carried out. The research results are used to develop lecture method innovations, to improve the quality of the lecture process. Students’ perceptions of the ability of lecturers, the activeness of learning, the environment of learning, and the absorption of lecture material are the problems examined in this study. The research method used was quasi-experimental, and the student perception data were obtained using a questionnaire given to 20 students as respondents. In addition, qualitative methods are used to analyze student perception data. The analysis results used a score on a scale of 1-4, obtained an average score of students’ perceptions of the ability of lecturers by 3.78, learning activeness 3.15, learning environment 3.43, and absorption of lecture material 3.49. The conclusion is that lecturers’ ability to manage lectures is excellent, students are active in lectures, the learning environment is pleasant, and absorption of higher lecture material. Therefore, discussion method innovation can be developed to enrich the learning method to improve the quality of the Thermodynamics lecture process.